THE EVOLUTION OF MARKETING MANAGEMENT IN AN ENTERPRISE (Development Service Industry Management, 2023)
The article examines the essence of the concept of "marketing". Marketing is understood as a complex activity aimed at meeting the needs and requests of consumers through the creation, promoting and salling of goods / services. The concepts of marketing are considered. In particular, the production concept aimed at increasing production volumes due to increased labor productivity, effective use of resources, and also cost reducion; a product concept aimed at improving the quality and functionality of products manufactured by the enterprise in order to satisfy consumer needs; a sales-oriented concept that is focused on sales promotion; the concept of traditional marketing, which focuses on meeting the needs of consumers, as well as on understanding their desires and creating value for them; the concept of social marketing stresses the responsibility of enterprises towards society and the importance of protecting the environment and social aspects of their activities; the concept of relations based on the creation and maintenance of long-term relations with clients and interaction with them at all stages of relationships; concepts of digital marketing based on the development of digital technologies and customer relationships, as well as taking into account the influence of social networks and online communications. The article states that these concepts reflect the evolution of marketing, and modern companies use a combination of these concepts to succeed in the market and guarantee consumer satisfaction. Marketing concepts of well-known companies were analyzed by the author.
Keywords: marketing; marketing concepts; production concept; product concept; sales-oriented concept; traditional marketing concept; social marketing concept; relationship concept; digital marketing concept